Perception, our freedom of action versus consciousness regarding social media and website - Mohd Saifur Rahman; Zobaid Mohammad Rahat Chowdhury; Mahmuda Ahmed; Md Ferdous Rabbi; Faisal Mahmud Pasha; Iren Billah; Taslima Ahmed Dola (Update Dental College, 2022)
Objectives: Apart from the benefits, social media also brings threats to teenagers. They are at risk if they access the internet under the age they are not allowed without their parent's permission. Children and teenagers widely use social media and recent studies have shown that they spend the majority of their time daily on social media pages. This study aimed to evaluate whether our freedom of action has increased but not consciousness regarding social media and websites. Materials and Methods: This descriptive cross-sectional study was conducted among the students, teachers, and clinical doctors of East-West Medical College and Hospital and elite society of some areas at Uttara Model Town, Dhaka during the period from January 2018 to April 2018. A total of 365 purposively selected respondents were included in this study. After taking consent from the respondent data were collected by self-administered written questionnaire. Data were checked, cleaned, and edited to find any inconsistencies before entering into the computer. Analyses of data were done using computer software SPSS version 23.0. Analyzed data are presented by appropriate tables and charts. For qualitative data frequency distribution was shown. For the quantitative variables, different statistics (mean, median, mode, standard deviation, etc.) were calculated. Results: There were altogether 23 statements and it was seen that most of the respondents agreed with the statements. The proportion of consent ranged from 52% to almost 99%. In the cases of 12 statements, it was above 90%. In cases of 6 statements, it was from 80% to 89%. In cases of 3 statements, it was from 70% to 79%. Only one statement had a proportion of consent of 69.3% and only one had 52.1%. Most (95.6%) of the respondents mentioned that one major mental fluctuation of the young due to excessive smartphone use was 'detachment from family and society. Another important mental fluctuation was 'aggressive attitude' as mentioned by 68.8% of the respondents. Nearly half (47.1%) of the respondents mentioned 'depression'. Other mental fluctuations of the young due to excessive smartphone use were 'apathy', 'jealousy', and 'lack of love and respect for elders' as mentioned by 26.6%, 19.2%, and 5.2% of the respondents respectively. Conclusion: There are positive and negative impacts of using the internet and different social media. But problems start when someone indiscriminately uses the internet or social media or when one uses those excessively. Aggressive attitude, detachment from family and society, apathy, depression, jealousy, lack of love, and respect for elders may be due to excessive social media use. However, it is clear that social media affects people differently, depending on preexisting conditions and personality traits. But at the same time, it would be wrong to say that social media are universally bad things because it brings myriad benefits to our lives. Update Dent. Coll. j: 2022; 12(1): 32-36